Determinants of Performance in Mathematics among Learners with Hearing Impairement in Special Secondary Schools in Kenya - Owino, Cleophas Owiko (JOOUST, 2018)
For long, there have been various arguments about how children who are deaf should be taught. Debate about whether to use sign language, speech, signs in English word order, created sign systems or bilingualism have been going on. Stakeholders in the field of deaf education have been reconciling the differences in each of those perspectives and determining how to proceed with their education. This has somehow projected into their learning hence academic lag. The subject possibly highly affected with this phenomenon is mathematics where the results of learners with hearing impairment at KCSE examinations have continued to be progressively below average. This study was designed to explore determinants of performance in Mathematics among learners with hearing impairment in special secondary schools in Kenya. The study was guided by four objectives: To establish the influence of teaching and learning resources on mathematics performance among learners with hearing impairment in special secondary schools, to determine the influence of teacher factor on mathematics performance among learners with hearing impairment in special secondary schools; to find out the influence of parental participation on mathematics performance among learners with hearing impairment in special secondary schools; to establish the influence of linguistic factor on mathematics performance among learners with hearing impairment in special secondary schools in Kenya. The study was informed by Vygotsky's Socio-cultural Theoretical Perspective (1978) and a Conceptual framework. The multiple case study research design was adopted for the conduct of the study. It was conducted in three secondary schools for the hearing impaired in the lake region (formerly Nyanza Province) in Kenya. The target population was 499 respondents which comprised of 3 principals, 37 teachers, 444 students, the 12 form one to form four PT A class representatives from the three schools and three CSOs. The sample size was 48 informants which was comprised of 3 principals, a total of 12 mathematics teachers, 24 form three students from the three schools, 6 PA representatives and the 3 CSOs from the three sub-counties. Sampling techniques used were saturated, stratified and purposive sampling. The research tools were interview schedule, Focus Group Discussion, observation check] ist and document analysis. Trustworthiness of qualitative data was ensured using triangulation, thick description and member checking strategies. The qualitative data collected was analyzed using thematic framework approach. The findings: On the issue of influence of teaching and learning resources on mathematics performance, the study found out that there were inadequate resources being used. On the concern about teacher factors influencing mathematics performance, the themes on teacher factors that emerged were: there were few mathematics teachers, teachers' knowledge and use of sign language was not adequate, there were few teacher-learner consultations, teachers' mode of delivery and teacher refresher course were inadequate. With reference to influence of parental participation on mathematics performance the study found that there was gross lack of assistance with homework which should be practiced by the parents. Parental collaboration and consultations with the teachers in the school was also very minimal, Parental communication with the school and participation in decision making were quite demanding. The findings on linguistic factors include: verbal language deficit among deaf learners, abstractness of words and difficulty in applying Kenya Sign Language to learn and perform mathematics tasks. The study conclusively found out that the themes on teacher factor were paramount in influencing mathematics performance among learners with hearing impairment in comparison to other factors under study. It was recommended that the government to staff special secondary schools for the deaf with teachers who are qualified in deaf education so as to improve performance in subjects like mathematics.